Re-purposing fika: rest, recreation or regulation in the neoliberalized Swedish University?. Issue 4 (2nd October 2018) - Morley, Louise; Angervall, Petra; Berggren, Caroline; Dodillet, Susanne
ABSTRACT: Fika is the Swedish practice of assembling for a coffee break at work or home. This paper investigates the material, social and temporal investments in fika in accelerated and accountable organizational cultures, and asks what purpose it serves in neoliberalised academic employment regimes today. Analysis of our thirteen interviews with administrators and academics in a Faculty of Education in a large research-intensive Swedish university suggests that there are multiple interpretations of fika. Traditionally, fika has been used as a site for team-building, democratization, and well-being at work, but might have been re-purposed and incorporated in neoliberal surveillance and normalization technologies in which one's corporate loyalty and interpersonal skills are made visible for assessment. We noted an affective and gendered economy with fika eliciting feelings of pleasure in the social and recreational aspects, but shame and anger at what was perceived as coercion to perform a particular type of sociable subjectivity.